Between myth and logos: interpretation of the importance of myth for the inception of the concept of economy - Edward Andrés Tamayo Duque (Escritos, 2017)
Unlike what happens nowadays, Economy in Ancient Greece was not seen as a branch of science dedicated to the study of trade, wealth or distribution of resources. On the contrary, it was a domestic issue. For Ancient Greeks, home was the center of their responsibilities as good citizens: governing themselves and governing their proprieties. The aim of the article is to analyze the primitive origin of economic practices within the myths of Hestia, Hermes, Demeter, and Cybele. Therefore, beginning with the etymological root of the word, an interpretation of these four gods is proposed, which provides elements to argue that the concept of Economy appears earlier than the Socratic discourse of the Classical Period. Through an interpretation of the myth, it is also possible to identify some signs that outline a series of practices, which subsequently were crucial to attach a value to this particular concept.